The effect of hand arm vibration symptoms among palm oil harvester with the usage of cantas machine in Selangor - Mohd Fadzil, Mohd Noraiman; Md Tamrin, Shamsul Bahri (Human Factors and Ergonomics Society Malaysia, 2019)
A cross sectional study was conducted to determine the effect of hand arm vibration symptoms on ‘Cantas’ machine among palm oil harvester in Selangor.Questionnaire survey is use as strategy of enquiry for achieving the objectives. A vibration analyser HVM 100 attached to a tri-accelerometer was used.The vibration level for working hours is 2.30 m/s2and is deemed safe as specified in ISO 5349-1. The prevalence of hand-arm vibration syndrome(HAVS)based on reported symptoms through questionnaires was 39.4%. None of them reported persistence in the symptoms. The ergonomics risk factor mean score was 2.93 out of 4. The issues on ergonomic design was weight, maintenance, portability, ease of usage and efficiency. In conclusion, regular screening for early signs of vibration-related damage is needed as an important part of preventing the aggravation of health problems. The workers also gained awareness regarding vibration exposure and safe working procedure on using Cantas machine.